2022
DOI: 10.3389/feart.2022.823540
|View full text |Cite
|
Sign up to set email alerts
|

Variation of Thermal Infrared Brightness Temperature Anomalies in the Madoi Earthquake and Associated Earthquakes in the Qinghai-Tibetan Plateau (China)

Abstract: We processed MODIS data received from ground receiving stations into the spatial range of the Qinghai-Tibetan Plateau (China) and the eastern margin of the plateau, and then 283 K was set as the threshold value to remove the area covered by clouds. The monthly background field was calculated based on 17 years’ data, then we obtained the spatial Brightness Temperature anomaly of the current month by deducting the background field. Furthermore, the Brightness Temperature anomaly curves for secondary tectonic blo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 46 publications
(73 reference statements)
0
6
0
Order By: Relevance
“…3(i)), the BT radiation intensified again, predominantly in the eastern Qiangtang and eastern Bayan Har blocks, approximately 32% and 14% of which experienced an increase in BT above the threshold, respectively. Available research findings suggest that spatial radiation intensification gradually disappears after an earthquake [40]. However, as seen in Fig.…”
Section: Resultsmentioning
confidence: 93%
See 2 more Smart Citations
“…3(i)), the BT radiation intensified again, predominantly in the eastern Qiangtang and eastern Bayan Har blocks, approximately 32% and 14% of which experienced an increase in BT above the threshold, respectively. Available research findings suggest that spatial radiation intensification gradually disappears after an earthquake [40]. However, as seen in Fig.…”
Section: Resultsmentioning
confidence: 93%
“…Images of each swath were then cropped based on the size of the study area, and the BT was retrieved simultaneously. The cropped images were combined into images with a temporal resolution of 1 day [40]. Since cloud cover is detrimental to the > TGRS-2022-03662 < retrieval of the BT, a cloud removal procedure is also required to process the MODIS BT data.…”
Section: A Dataset and Processingmentioning
confidence: 99%
See 1 more Smart Citation
“…In comparison, lower ILRA values were observed within the five tectonic blocks in 2019 when earthquakes of M > 5.5 did not occur (blue lines in Figure 10). Using MODIS monthly brightness temperature data, Yang et al [37] observed two increased thermal anomaly processes in the Tibetan Plateau prior to the Madoi earthquake, which started from June 2020 and January 2021, and they found that the anomalies moved from west to east with time. Our results based on MWBT and OLR data with higher temporal resolutions shed further light on the thermal evolution within the different scale tectonic units (seismogenic fault and active tectonic block) during the second thermal anomaly process since January 2021.…”
Section: Discussionmentioning
confidence: 99%
“…The thermal-related signals associated with this earthquake have been reported using the MODIS infrared brightness temperature (IRBT) and AMSR2 microwave brightness temperature (MWBT) data [37,38]. The infrared variation has shown that an increased IRBT has covered most areas of Tibetan Plateau since October 2020 [37], and an enhancement in MWBT within the Bayan Har block, which is more pronounced compared to the outside of this block, has been observed since January 2021 [38]; this may be associated with the localized activities in this block.…”
Section: Madoi (China) M 73 Earthquakementioning
confidence: 99%